El aprendizaje significativo y su incidencia en el rendimiento académico de los estudiantes de 3ro EGB de la UE Sofía Alarcón, Babahoyo. 2022 - Alcívar Almeida, Maria Elena (2022)
The purpose of the case study is to investigate how significant learning influences the academic performance of third-year EGB students of the Sofia Alarcon Educational Unit in the city of Babahoyo, for this purpose the analysis of the current situation of the Educational Unit this procedure allowed to concatenate the study variables with the theoretical support of the study, developed these steps we proceed to the collection of information in the surveys carried out on the teachers, where they contributed with the research work, where we found that the factors that cause the low performance of the students are shortcomings in the teaching strategies of the teachers who do not adapt the concepts to examples of daily life, this was verified in the taking of surveys. To strengthen the research, it is recommended to expand the study population within the educational center in order to obtain a greater amount of data that would logically provide more consistent analysis tools in relation to meaningful learning with the academic performance of the students.